Mechanical and Microstructural Properties of Geopolymer Paste from High Calcium Fly Ash Containing Basalt Fiber Powder from Waste Insulation - Saptamongkol, Adam; Nasaeng, Phaithun; Wongsa, Ampol; Kroehong, Wunchock; Sata, Vanchai; Chindaprasirt, Prinya (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2024)
In this study, the properties of geopolymer paste from high calcium fly ash replaced by basalt fiber powder from insulation waste at the rates of 0, 10, 20, 30, and 40 wt% were evaluated. The activator with sodium silicate to sodium hydroxide (10 Molar) ratio (NS/NH) at 1.0 and the liquid to binder (L/B) ratio at 0.6 were used. The curing of the paste sample was conducted at room temperature. The setting time, compressive strength, flexural strength, and microstructure were tested. The results showed that all the geopolymer paste mixtures had SiO2/Al2O3 molar ratios between 3.79 and 4.49. The setting time of the paste was prolonged with increasing basalt fiber powder content. This is due to the reduction of calcium silicate hydrate (C-S-H) and calcium (alumino) silicate hydrate (C-(A)-S-H) in the mixture. The compressive strength of 20 % basalt fiber powder paste (BP20) gave the highest compressive strength with the compressive strength of 32.0, 53.6, and 68.0 MPa at the test ages of 7, 28, and 90 days, respectively. The flexural strength increased significantly with the increase in the amount of basalt fiber powder. In addition, replacing fly ash with basalt fiber powder at a ratio not exceeding 20 % helps the gel of geopolymer paste to form more new crystals, resulting in a denser structure that increases the paste's strength.